Beckman Facilities, Austria (1968)
Beckman Instruments, G.m.b.H. was established in 1968. The pictured Viennese estate was initially shared by Beckman Instruments and the family of manager Ulf Daum, but as the company expanded the Daums relocated. The photograph was taken before the late 1980s, when the company moved out of the city.
Keywords: Buildings; Trucks; Beckman Instruments, Inc.